Depressed mood affects the process of biological aging, analyses from the NHANES dataset - Tian, Yuan; Lu, Qiao; Li, Jing; Zhou, Xiaobo; Wang, Luyao; Zhong, Xuemei; Luo, Yiping (Frontiers in Aging, 2025)
BackgroundDepressive mood may influence biological aging and the difference (δ-age) between biological age (BA) and chronological age (CA). This study explores the relationship between depressive mood and whole-body delta age (δ-age).MethodsA total of 7,383 U.S. adults were selected from the National Health and Nutrition Examination Survey (NHANES) conducted between 2007 and 2018. Depressed mood was evaluated using PHQ-9 scores. Biological age (BA) was estimated based on circulating biomarkers, and the calculated delta age (δ-age) was validated through a generalized linear regression analysis.ResultsAfter adjusting for confounding variables, logistic regression analysis demonstrated a significant association between elevated depressive symptoms and accelerated biological aging. The restricted cubic splines (RCS) results further indicated a positive dose-response relationship between depression scale scores and the risk of biological aging. Additionally, the weighted quantile sum regression (WQS) findings revealed a positive, though non-significant, trend linking depressive mood to the risk of biological aging. Notably, overeating and low self-perception emerged as the most significant contributors to the scores on the Patient Health Questionnaire-9 (PHQ-9) scale.ConclusionDepressive symptoms are linked to accelerated biological aging. Thus, interventions aimed at improving mood may help slow biological aging and contribute to delaying the aging process.